2021
DOI: 10.1016/j.esmoop.2021.100115
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter cohort study of osimertinib compared with afatinib as first-line treatment for EGFR-mutated non-small-cell lung cancer from practical dataset: CJLSG1903

Abstract: Background: FLAURA, the prospective trial of osimertinib as a first-line therapy compared with first-generation epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs), did not show superior survival benefit for osimertinib in either the subgroup of Asians or the subgroup with the L858R mutation. In addition, the superiority of osimertinib compared with second-generation EGFR-TKI is thus far unclear. Patients and methods: We reviewed the clinical data of all consecutive patients who were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 19 publications
1
34
0
4
Order By: Relevance
“…No prospective study comparing osimertinib with 2G EGFR-TKIs is available. The only retrospective study demonstrated that osimertinib and afatinib showed similar OS [ 47 ]. Because it has a high price and offers no survival benefit in an Asian subgroup [ 11 ], osimertinib is not fully reimbursed in Asian countries, including Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…No prospective study comparing osimertinib with 2G EGFR-TKIs is available. The only retrospective study demonstrated that osimertinib and afatinib showed similar OS [ 47 ]. Because it has a high price and offers no survival benefit in an Asian subgroup [ 11 ], osimertinib is not fully reimbursed in Asian countries, including Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Third, the recent advance of third-generation EGFR-TKIs also challenges the role of afatinib as a front-line treatment. Interestingly, a recent study of a Japanese cohort demonstrated that afatinib resulted in better OS compared with osimertinib, 41 though this issue remains largely unsettled.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the recent administration of third-generation osimertinib monotherapy as well as the combination of osimertinib and bavaciumab also challenges the role of afatinib on the treatment of advanced EGFR -mutant NSCLC [ 36 , 37 ]. However, a recent Japanese real-world cohort of NSCLC patients demonstrated an improved OS of front-line afatinib compared to osimertinib treatment [ 38 ] and the true benefit of adding bevacizumab to front-line osimertinib remains largely unsettled based on some small early-phase trials [ 37 ].…”
Section: Discussionmentioning
confidence: 99%